Usage of Natural Health Products (NHPs) for respiratory diseases: user characteristics and NHP-Consumption behavior during the Covid-19 pandemic in Germany - Miriam Wolf; Agnes Emberger-Klein; Klaus Menrad (BMC, 2023)
Abstract Background Respiratory diseases (RD) can challenge healthcare systems around the globe. Natural health products (NHPs) are popular complementary and alternative medicine options for health issues concerning non-fatal RD. Little is known about the characteristics of the users of RD-NHPs and about their NHP consumption behavior during the Covid-19 pandemic in Germany. Methods A representative online survey was conducted in Germany in 2022. 1707 participants were classified based on having used NHPs for RD within the previous 12 months, having used NHPs but not for RD within the previous 12 months and not having used NHPs. Data were analyzed using descriptive and inferential statistical methods as well as a multinomial logistic regression model. Results Users of RD-NHPs within the previous 12 months were more likely to be employed and to consult pharmacists more often for non-fatal health issues than individuals who did not take RD-NHPs. RD-NHP users were more likely to suffer from a Covid-19 infection and to have children living in the same household than other NHP users. Compared to non-NHP users, RD-NHP users were more likely to be female, highly educated and have stronger openness-to-change value orientations. Vaccination-related behavior was no indicator of RD-NHP usage. Most RD-NHP users took NHPs in self-medication. Few reported informing their practitioner about their self-medication. Drugstores were the most visited supply source for NHPs during the pandemic, followed by pharmacies. Common information sources regarding NHPs were the products themselves and pharmacists. Conclusion This study emphasized the important role of NHPs as a popular prevention and treatment option for RD. RD-NHPs were more likely used by individuals who were employed, who suffered from a RD and who consult pharmacists for non-fatal health issues. The importance of product information and pharmacies as information sources should be considered to make communication strategies about safe self-medication options with RD-NHPs more effective, which could help to reduce the burden of health facilities regarding non-fatal RD. To improve and develop future pandemic-control strategies, health professionals and policy makers should consider NHP usage behavior and provide critical information about chances and risks of self-medicated NHP consumption.